KERJASAMA PERPUSTAKAAN UNIVERSITAS PENDIDIKAN INDONESIA (UPI) DENGAN KOREA-INDONESIA CULTURAL CORNER (KICC) DALAM UPAYA PENGEMBANGAN KOLEKSI - Siti Aminah Julianti; Asep Saeful Rohman (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2023)
This research aims to investigate how the principles of collection development and the stages of collection development are implemented in the collaboration between the University of Education Indonesia (UPI) Library and the Korean-Indonesian Cultural Corner (KICC). It also seeks to identify the impacts and challenges encountered during the implementation of this collaboration. The research method employed in this study is descriptive qualitative research. Data were gathered through observations and interviews with the library managers. The collected data were analyzed to comprehend the dynamics of the collaboration and the implementation of collection development principles. The findings of the research reveal that the UPI Library has not fully applied the principles of collection development in the services provided by the Korean-Indonesian Cultural Corner (KICC). One of the major challenges identified is the lack of effective communication between the UPI Library and KICC. This has resulted in discrepancies in the stages of collection development and a limited understanding of collection priorities. The impact of these challenges is a less efficient and effective collection development process. Therefore, to maximize the outcomes of this collaboration, efforts are needed to expand and enhance communication between the UPI Library and KICC. This will assist in understanding the needs and expectations of each party, enabling a more efficient implementation of collection development stages. Additionally, regular evaluations should be an integral part of this collaboration to ensure the expected impacts are achieved.